Karcinoza možganskih ovojnic in rak dojk - Žnidarič, Tanja (Onkologija (Ljubljana), 2019)
Introduction: Leptomeningeal carcinomatosis (LMC) develops with infiltration of leptomeninges by malignant cells and means poor prognosis. Radiotherapy presents one of the treatment options for neurological symptom relief. Methods: We retrospectively analyzed 423 patients with breast cancer (BC) and brain metastasis (BM) or LMC, who received radiotherapy of the brain between the years 2005 and 2015 at the Institute of Oncology Ljubljana. We analyzed patients with LMC in more detail and performed a validation of prognostic survival indexes, namely Breast Graded Prognostic Assessment (Breast-GPA) and Simple Survival Score for Brain Metastases (SS-BM). Results: Seventy patients with LMC were treated with whole-brain radiotherapy in the observed time. Median time from BC diagnosis to LMC appearance was 4.3 years and was shortest in triple-negative and longest in luminal A BC subtype. Median overall survival for patients with BM and LMC was 7.5 (95 % confidence interval, CI; 6.3%8.8) and 2.3 months (95 % CI; 1.5%3.2), respectively (p 20 Gy). Breast-GPA (p < 0,005) and SS-BM (p = 0,044) indexes predicted survival with statistical significance. Conclusions: Performance status, BC molecular subtype and prognostic indexes were all factors influencing expected survival in our group of analyzed LMC patients.
Keywords: breast cancer; karcinoza možganskih ovojnic; leptomeningeal carcinomatosis; obsevanje; radioterapija; radiotherapy; rak dojke